2018
DOI: 10.1055/s-0038-1675837
|View full text |Cite
|
Sign up to set email alerts
|

A Turkish Female Twin Sister Patient with Fibular Aplasia, Congenital Tibia Pseudoarthrosis, Oligosyndactyly, and Negative WNT7A Gene Mutation

Abstract: We report a rare limb defect named as fibular aplasia, tibial campomelia, and oligosyndactyly (FATCO) syndrome in a female monozygotic twin with a normal twin sister, presented with anterior tibia pseudarthrosis, oligosyndactyly, and pes equinovarus. Radiographic examination displayed the absence of left fibulae, anterolateral pseudarthrosis of left tibia, and the absence of some metatarsus and phalangeal bones. Our case report is the first to report that only one of the identical twins was affected by FATCO s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Hence, despite having the same DNA sequence how did FATCO syndrome happen in one of the monozygotic twin sisters. Hence we can say that FATCO syndrome does not occur only due to a gene mutation but also by other unknown mechanisms [ 6 ]. Moreover, one case report also has found the correlation of chromosomal aberration with FATCO syndrome [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, despite having the same DNA sequence how did FATCO syndrome happen in one of the monozygotic twin sisters. Hence we can say that FATCO syndrome does not occur only due to a gene mutation but also by other unknown mechanisms [ 6 ]. Moreover, one case report also has found the correlation of chromosomal aberration with FATCO syndrome [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since monozygotic twins have the same DNA, it could be said that "FATCO" is not only due to DNA mutations but other mechanisms also play an important role. 14 Since our patient had no significant perinatal history, any family history of limb abnormalities, or any similar condition in any of the four siblings, this suggests that the syndrome occurred sporadically. Similarly, the mode of inheritance of this disease is also unclear.…”
Section: Discussionmentioning
confidence: 73%
“…Until our study, no systematic larger sequencing analyses have been reported in a cohort of individuals with FATCO syndrome. In our cohort, we performed exome sequencing followed by genome Yilmaz et al, 2019). Hecht and Scott reported half siblings with limb deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, chromosome analysis was performed (16 reported cases) which has been normal, aside from the case with Klinefelter which showed 47, XXY (Capece et al, 1994; Courtens et al, 2005; Ekbote & Danda, 2012; Hecht & Scott, 1981; Isik et al, 2019; Izadi & Salehnia, 2020; Kitaoka et al, 2009; Marinho et al, 2020; Nogueira et al, 2016; Sezer et al, 2014; Yucel Celik et al, 2021). In six cases microarray was performed and normal (Isik et al, 2019; Izadi & Salehnia, 2020; Marinho et al, 2020; Nogueira et al, 2016; Önder Yilmaz et al, 2019; Sezer et al, 2014; Yucel Celik et al, 2021). In few cases, WNT7A analysis was performed and normal (Kitaoka et al, 2009; Önder Yilmaz et al, 2019; Yucel Celik et al, 2021) and in one case each TP63 , WNT10B , and NF1 analysis was completed and normal (Bieganski et al, 2012; Önder Yilmaz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation